Health and Illnes Concept in Elderly Age in Munte Village, Munte District, Karo Regency - Mia Audia Br Kaban; Nurman Achmad (Indonesian Journal of Medical Anthropology, 2021)
Abstract: This study discusses the concept of health and illness in the elderly in Munte Village, Munte District, Karo Regency. The purpose of this study was to see how the elderly respond in dealing with disease and to see what things are done to process the prevention and cure of a disease. The method used in this research is ethnography with a qualitative approach with the aim of systematically describing cultural characteristics more deeply in their own space and time. The methods used in data collection are participatory observation and unstructured interviews and use interview guidelines. The results of the study were to see how the elderly interpret health in old age. Traditional medicine that is so attached to their daily lives is a knowledge that is passed down from generation to generation. The role of the family is very important in supporting the health of the elderly both from a social, economic and psychological perspective.